Sand production simulation under true-triaxial stress conditions - Younessi, Ahmadreza; Rasouli, Vamegh; Wu, Bailin (Pergamon, 2013)
Laboratory sanding experiments were carried out under true-triaxial stress conditions. The objective was to investigate the effect of state of stresses and fluid flow on the mechanism of sanding, and the development of the failure zone around the borehole. The experiments were conducted on 100×100×100 mm3 cubic samples of synthetic sandstones. The samples were prepared based on an established procedure developed to produce weakly consolidated sandstone samples with identical physico-mechanical properties. The properties of the synthetic sandstone samples were determined by conducting a series of standard rock mechanics tests on cylindrical plugs. Using a true-triaxial stress cell (TTSC), cubic samples were subjected to true-triaxial stresses and radial fluid flow from the outer boundaries into the borehole. The maximum and intermediate principal stresses were applied laterally in both cases while the effect of changing the lateral stresses on the development of the failure zone around borehole was monitored. It was observed that the geometry (i.e. width and depth) of the failure zone developed around the borehole is a function of the lateral stresses ratio (i.e. lateral stress anisotropy). The experiments were also simulated numerically using ABAQUS in order to validate and interpret the results from the experiments. A good agreement was obtained between the results of both methods, which confirms the importance of lateral stress anisotropy on the evolution of sanding. The observations and results of these experiments and numerical simulations will be presented and discussed.